THE EFFECTS OF PERCEPTION USING AUTHENTIC MATERIAL AND LEARNING AUTONOMY TOWARDS STUDENTS’ COLLOCATION AWARENESS - Irma Wahyuni (JELLi Journal, 2022)
This research is a kind of survey and aims to find out and analyze empirically the effects of student’s perception on using authentic material and autonomous learning towards student’s collocation awareness. The observed population of this research is students of private vocational schools in Bogor. The sample was gained through simple random sampling, which means that the researcher mixed the subjects in the population so that they will be considerably the same. This research has 3 variables which are divided into 2 independent variables (student’s perception on using authentic material and autonomous learning) and 1 dependent variable (collocation awareness). The collection of the data is done by questionnaire and objective tests for both independent and dependent variables. The gained data was then analyzed by using correlation technique and multiple regressions. Previously, the prerequisite tests before examining the regression test must be accomplished, such as normality test and linearity test. The result of this research is: 1) There are significant effects of student’s perception on using authentic material and autonomous learning altogether towards student’s collocation awareness and it is proved by Fo = 42.383 and Sig.=0.000 < 0.05; 2) There is a significant effect of student’s perception on using authentic material towards student’s collocation awareness and it is proved by to = 4.889 and Sig.=0.000 < 0.05; 3) There is a significant effect of autonomous learning towards student’s collocation awareness and it is proved by to = 5.188 and Sig.=0.000 < 0.05. It means that the student’s collocation awareness is strongly influenced by student’s perception on using authentic material and autonomous learning of his/her own..